2011
DOI: 10.5173/ceju.2011.02.art6
|View full text |Cite
|
Sign up to set email alerts
|

SEXUAL DISORDERS Our experience in the treatment of priapism

Abstract: Priapism is a persistent erection without sexual stimulation that cannot be relieved by orgasm. Its etiology includes the impaired mechanism of detumescence caused by the abundant release of neurotransmitters, venules obstruction, impairment of the intrinsic mechanism of detumescence, or prolonged relaxation of the intracavernous smooth muscles. Treatment of priapism is conservative, pharmacological, or surgical. Efficient treatment options include the intracavernous vasoconstrictor injections or surgical shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some are idiopathic. [ 9 10 11 12 13 ] In our series, all the cases were of ischemic type with varied etiologies. Mean duration of priapism was 96.7 h. Late presentation to medical facilities was due to patient's embarrassment and poor knowledge about the condition attributed to this prolonged duration of priapism at presentation.…”
Section: Discussionmentioning
confidence: 71%
“…Some are idiopathic. [ 9 10 11 12 13 ] In our series, all the cases were of ischemic type with varied etiologies. Mean duration of priapism was 96.7 h. Late presentation to medical facilities was due to patient's embarrassment and poor knowledge about the condition attributed to this prolonged duration of priapism at presentation.…”
Section: Discussionmentioning
confidence: 71%
“…Detumescence rates varied among studies depending on the time interval between IP onset and shunt surgery. In 5 studies ( (14,(17)(18)(19)45)) where median IP duration was ≤36 hours, success rates ranged between 77.7 and 100%. An overall complication rate of 18%.…”
Section: Distal Shuntsmentioning
confidence: 99%
“…Analysis of the literature has shown that scalpel-based shunts (eg, Ebbehoj, Al Ghorab, Lue T Shunt) provide higher success than needle-based (ie, Winter's) shunts. 5,15,18,24–38 Another potential factor relevant to comparative success rates is duration of priapism prior to the intervention of interest. In one study of patients managed with tunneling, detumescence was achieved in 100%, 34%, and 0% of cases treated before 24 hours, at or beyond 48 hours, and at or beyond 96 hours, respectively.…”
Section: Guideline Statementsmentioning
confidence: 99%